Clinical outcomes related to fasting plasma glucose variability, history of diabetes mellitus and antidiabetic regimens in patients with atrial fibrillation: a subgroup analysis from the SPORTIF trial. (25th November 2020) - Proietti, M; Gumprecht, J; Farcomeni, A; Romiti, G.F; Lip, G.Y.H
Abstract: Introduction: The role of diabetes mellitus in determining of major adverse outcomes in patients with atrial fibrillation (AF) is well-established. Little is known about fasting plasma glucose (FPG) visit-to-visit variability (VVV) and its impact on outcomes. Aim: To analyse the role of FPG-VVV in determining major adverse outcomes in AF patients. Second, to evaluate the prognostic impact of history of diabetes mellitus and antidiabetic regimens. Methods: Warfarin-treated patients from the SPORTIF trials were considered for analysis if they had FPG evaluation at baseline and at least 4 determinations throughout follow-up. Standard deviation (SD) of the mean of FPG throughout follow-up was the main measure of VVV, according to its quartiles (SD-Qs). A composite of cardiovascular events and the occurrence of all-cause death was the adverse outcome considered. Results: Among the 3665 patients originally included, 3415 (93.2%) were included in this analysis. Throughout a mean (±SD) of 577.59 (±122.09) days of follow-up patients in the highest SD-Q (SD-Q4) had the highest rate of the composite outcome and all-cause death [Figure]. A Cox multi-regression analysis confirmed that SD-Q4 had a significant independent association with occurrence of composite outcome (hazard ratio [HR]: 1.61, 95% confidence interval [CI]: 1.10–2.35) [Figure, Upper Panel], with a non-significant trend for all-cause death, [Figure, Lower Panel]. If no significant impact of history of diabetes mellitus was found, there was a significant impact on the composite outcome of the various antidiabetic regimes: there was no difference found in patients treated with oral antidiabetics, compared to no antidiabetic treatment, but those patients treated with insulin (±oral antidiabetics) were independently associated with the occurrence of composite outcome (HR: 2.38, 95% CI: 1.05–5.38) (Table). Conclusion: In AF patients treated with warfarin, patients with the highest FPG-VVV had an increased rate of outcomes and the largest FPG-VVV being significantly associated with the composite outcome of adverse clinical events. In diabetic patients, use of insulin is independently associated with an increased risk of the composite outcome, reflecting the more severe disease in determining adverse events amongst AF patients. Funding Acknowledgement: Type of funding source: None